Referrers' point of view on the referral process to neurosurgery and opinions on neurosurgeons: a large-scale regional survey in the UK. Issue 11 (26th November 2017) - Amarouche, Meriem; Neville, Jonathan J; Deacon, Simon; Kalyal, Nida; Adams, Nikita; Cheserem, Beverly; Curley, Daniel; DeSouza, Ruth-Mary; Hafiz, Fehmi; Jayawardena, Tanya; Khetani, Nishi; Matthews, Diana; et al.
Abstract : Objectives: There is an increased reliance on online referral systems (ORS) within neurosurgical departments across the UK. Opinions of neurosurgeons on ORS are extensively reported but those of referrers have hardly been sought. Our study aims at ascertaining our referring colleagues' views on our ORS and its impact on patient care, their opinions on neurosurgeons and how to improve our referral process. Setting: 14 district general hospitals and one teaching hospital. Participants: 641 healthcare professionals across a range of medical and surgical specialties including doctors of all grades, nurses and physiotherapists. Survey responses were obtained by medical students using a smartphone application. Results: Although 92% of respondents were aware of the ORS, 74% would routinely phone the on-call registrar either before or after making referrals online. The majority (44%) believed their call to relate to a life-threatening emergency. 62% of referrers considered the ORS helpful in informing patients' care and 48% had a positive opinion of their interaction with neurosurgical registrars. On ways to improve the ORS, 50% selected email/text confirmation of response sent to referrers and 16% to referring consultants. Conclusion: Our results confirm that referrers feel that using our ORS positively impacts patient care but that it remains in need of improvement in order to better suit our colleagues' needs when it comes to managing neurosurgical patients. We feel that the promotion of neurosurgical education and mitigation of the effects of adverse workplace human factors are likely to achieve the common goal of neurosurgeons and referrers alike: a high standard in patient care.